Pharmacological treatment of chorea in Huntington’s disease–good clinical practice versus evidence-based guideline - Reilmann, Ralf (Blackwell Publishing Ltd, 2013)
Recently, the American Academy of Neurology published an evidence-based guideline for the pharmacological treatment of chorea in Huntington’s disease. Although the progress in medical care because of the implementation of criteria of evidence-based medicine is undisputed, the guideline classifies the level of evidence for drugs to reduce chorea based on anchors in the Unified Huntington’s Disease Rating Scale-Total Motor Score chorea sum score, which were chosen arbitrarily and do not reflect validated or generally accepted levels of clinical relevance. Thus, the guideline faces several serious limitations and delivers clinical recommendations that do not represent current clinical practice; these are reviewed in detail, and arguments are presented why these recommendations should not be followed. To remedy the lack of evidence-based recommendations and provide guidance to a pragmatic symptomatic therapy of chorea in HD, a flow-chart pathway that follows currently established clinical standards based on expert opinion is presented. © 2013 Movement Disorder Society